2008
DOI: 10.1063/1.3025918
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation study of self-assembly of tethered V-shaped nanoparticles

Abstract: We use Brownian dynamics to investigate the self-assembly of single end tethered, laterally tethered, and double end tethered V-shaped nanoparticles. The simulation results are compared with model bent-core molecules without tethers and polymer tethered nanorods to elucidate the combined effects of V-shaped geometry and the immiscibility between the V-shaped nanoparticles and the tethers on the self-assembled structures. We show that the V-shaped geometry significantly alters the phase diagram of tethered nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…[31] Given the close relationship between tethered NPs and liquid crystals, [58] the roles of the shape of the NP head group have also been extensively investigated. [12,13,[67][68][69][70] In these cases, it was again found that structures and transitions similar to those in liquid crystals were observed, such as lamella, gyroids, cylinders, and micelles. However, the connectivity and coordination of the micelles and networks were altered by the packing of the head groups.…”
Section: Computational Design Of Functional Nanostructuresmentioning
confidence: 83%
See 2 more Smart Citations
“…[31] Given the close relationship between tethered NPs and liquid crystals, [58] the roles of the shape of the NP head group have also been extensively investigated. [12,13,[67][68][69][70] In these cases, it was again found that structures and transitions similar to those in liquid crystals were observed, such as lamella, gyroids, cylinders, and micelles. However, the connectivity and coordination of the micelles and networks were altered by the packing of the head groups.…”
Section: Computational Design Of Functional Nanostructuresmentioning
confidence: 83%
“…However, the connectivity and coordination of the micelles and networks were altered by the packing of the head groups. Additional types of liquidcrystalline ordering were found within these domains, such as long micelles and lamella, [69] twisted columns and sheets with liquid crystalline order, [12,13,67] honeycombs, [13] and gyroids. [68] The focus of recent studies has included increasing the architectural complexity of TNP building-blocks, including interactions between blocks and the solvent, as well as tuning their respective block volume fraction, thereby mirroring trends within the copolymer community.…”
Section: Computational Design Of Functional Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38][39][40] The model used for the present study, a schematic for which is provided in Fig. 1, consists of one flat rigid attractive surface, modeled by implementing the 10-4-3 Steele's potential, 41 and one spherical particle on which short polymer chains are grafted.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…123 This study was focused on the shape anisotropy of NCs. Other anisotropies could also arise from the asymmetrical functionalization of isotropic NCs (examples are Janus-, chiral and tethered nanoparticles [124][125][126][127][128][129] ), but those are beyond the scope of this work. …”
mentioning
confidence: 99%